Occurrence and Variations of Middle and Low Latitude Sporadic E Layer Investigated With Longitudinal and Latitudinal Chains of Ionosondes - Qiong Tang; Jiaqi Zhao; Zhibin Yu; Yi Liu; Lianhuan Hu; Chen Zhou; Zhengyu Zhao; Xueshang Feng (Space Weather)
Abstract A longitudinal chain and a latitudinal chain of ionosondes, located at Yakutsk (129.60°E, 62.00°N), Mohe (122.37°E, 53.50°N), Beijing (116.25°E, 40.25°N), Wuhan (114.61°E, 30.53°N), Sanya (109.42°E, 18.34°N), I‐Cheon (127.54°E, 37.14°N), San Vito (17.80°E, 40.60°N), Roquest (0.50°E, 40.80°N), Millstone Hill (71.50°W, 42.60°N), and Alpena (83.56°W, 45.07°N) ionosondes, are utilized to statistically investigate the sporadic E layer (Es) occurrence rate and variation. The Es occurrence rates at all stations show a similar dependence on local time and season. However, the seasonal dependence of Es occurrence is more distinct at middle latitudes than that at low latitudes along the 120°E longitude. Results at different stations along ∼40°N latitude show much lower Es occurrence at the American sector than that at European and East Asian sectors, which is most likely because the horizontal geomagnetic field in north America is smaller than in other regions. The statistical results demonstrate that the seasonal variations of Es occurrence and strength are related to the annual variation of meteor counts. Simulation results show that the summer maximum of the ion vertical drift velocity driven by the variations of neutral densities and winds could also contribute to the seasonal variations of Es occurrence and intensity. The seasonal variations of the quasi‐6‐day and quasi‐16‐day oscillations in Es are also investigated. The seasonal variations of periodic disturbances of the Es differ between each station. Planetary waves in the MLT region cannot fully explain the seasonal variations of the periodic disturbance of Es. Solar and geomagnetic activities can also result in periodic variations of the Es.